To find the distance between the points \((0, 6)\) and \((-3, -2)\), we can use the distance formula, which is derived from the Pythagorean Theorem. The formula is:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Here, \((x_1, y_1) = (0, 6)\) and \((x_2, y_2) = (-3, -2)\).
Now we substitute the coordinates into the formula:
-
Calculate \(x_2 - x_1\): \[ -3 - 0 = -3 \]
-
Calculate \(y_2 - y_1\): \[ -2 - 6 = -8 \]
-
Substitute these values into the distance formula: \[ d = \sqrt{(-3)^2 + (-8)^2} \] \[ d = \sqrt{9 + 64} \] \[ d = \sqrt{73} \]
Now, we can approximate \(\sqrt{73}\):
\[ \sqrt{73} \approx 8.54 \]
Thus, the answer, rounded to the nearest hundredth if necessary, is:
8.54